Prophylactic Human Papillomavirus Vaccination: From the Origin to the Current State - Ayazhan Akhatova; Azliyati Azizan; Kuralay Atageldiyeva; Aiymkul Ashimkhanova; Aizada Marat; Yerbolat Iztleuov; Assem Suleimenova; Saikal Shamkeeva; Gulzhanat Aimagambetova (Vaccines, 2022)
Immunization is the most successful method in preventing and controlling infectious diseases, which has helped saving millions of lives worldwide. The discovery of the human papillomavirus (HPV) infection being associated with a variety of benign conditions and cancers has driven the development of prophylactic HPV vaccines. Currently, four HPV vaccines are available on the pharmaceutical market: Cervarix, Gardasil, Gardasil-9, and the recently developed Cecolin. Multiple studies have proven the HPV vaccines’ safety and efficacy in preventing HPV-related diseases. Since 2006, when the first HPV vaccine was approved, more than 100 World Health Organization member countries reported the implementation of HPV immunization. However, HPV vaccination dread, concerns about its safety, and associated adverse outcomes have a significant impact on the HPV vaccine implementation campaigns all over the world. Many developed countries have successfully implemented HPV immunization and achieved tremendous progress in preventing HPV-related conditions. However, there are still many countries worldwide which have not created, or have not yet implemented, HPV vaccination campaigns, or have failed due to deficient realization plans associated with establishing successful HPV vaccination programs. Lack of proper HPV information campaigns, negative media reflection, and numerous myths and fake information have led to HPV vaccine rejection in many states. Thus, context-specific health educational interventions on HPV vaccination safety, effectiveness, and benefits are important to increase the vaccines’ acceptance for efficacious prevention of HPV-associated conditions.